Needs Analysis for Developing Ethnoscience-Integrated Project-Based Learning Chemistry Teaching Materials Supported by Digital Video on Macromolecule Topics in Senior High School - Anjany Tasya Surabika Br Tarigan; Siswanto Siswanto; Ramlan Silaban; Ani Sutiani (Journal of Educational Sciences, 2026)
This study aims to analyse the need for developing chemistry teaching materials based on Project-Based Learning (PjBL), integrated with ethnoscience and supported by digital video, for macromolecule topics in senior high school. The study employed a descriptive quantitative approach using a survey design involving 39 students and two chemistry teachers selected through purposive sampling. Chemistry textbooks used in schools were also analysed based on the Badan Standar Nasional Pendidikan (BSNP) criteria, including content, presentation, language, and graphical aspects. Data were collected through questionnaires and semi-structured interviews, and were analysed using descriptive statistics. The findings revealed that the aspects of content (3.20), presentation (3.05), language (3.30), and graphics (3.10) were categorised as moderate, while ethnoscience (2.70) and technology (2.60) were categorised as low. These findings indicate that the existing teaching materials have not optimally integrated local cultural contexts and digital learning support. Therefore, the development of ethnoscience-integrated chemistry teaching materials based on Project-Based Learning (PjBL) and supported by digital video is considered important to support more contextual, interactive, and meaningful learning experiences.